Dry Textile Forming Simulations: A Benchmarking Exercise - Sun, Xiaochuan; Belnoue, Jonathan P.-H.; Thompson, Adam; Said, Bassam El; Hallett, Stephen R. (Frontiers in Materials, 2022)
In this study, four representative finite element (FE) based modelling techniques and an analytical solution for the prediction of 2D woven fabrics’ deformation during forming are compared back-to-back. Ordered from high to low fidelity they are: 1/ a Multi-Filament (MF) method that sits between micro- and meso-scale that uses multiple beam element chains to represent each fibre yarn; 2/ a meso-scale 3D representation (3D-Shell method) that uses 2D structural shell elements to model each fibre yarn; 3/ a 2D continuum element approach that uses coincident membrane and shell elements with user defined material properties to capture the deformation response of textiles in an homogenised sense at the macro-scale; 4/ pin-jointed net (PJN) models where the reinforcement directions are represented by extendable 1D elements, pin-jointed at the elements’ crossover points. These modelling approaches are systematically compared for identical forming processes with identical process and material parameters such as boundary conditions, weave architecture and tooling geometries. For completeness and to highlight the importance of considering inter-yarn and preform-to-tool interactions, a kinematic drape algorithm (based on geometrical mapping) is also considered. An attempt is made to visualise the overall modelling performance and computational cost of all representative modelling approaches by simplified metrics.